2018
DOI: 10.1111/jop.12670
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory cytokines as serum biomarker in oral carcinoma—A prospective multi‐biomarker approach

Abstract: In conclusion, IL-6, IL-8, and sIL-2R are strongly associated with OSCC oncogenesis and IL-6 and sIL-2R seem to be promising and potent biomarkers for evaluating patients' prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 26 publications
2
26
0
Order By: Relevance
“…When analyzing our overall data, we observed an association between good prognosis and HPV positivity, whereas adverse prognosis was associated with increasing both CRP levels and WBC counts. These are expected associations that have been described in previous studies [ 9 , 21 , 22 , 23 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 78 ] and therefore suggest that our patient cohort is representative. Furthermore, histopathological features like tumor lymphocyte density predict prognosis both in HPV-negative and HPV-positive oropharyngeal cancer patients [ 79 ].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…When analyzing our overall data, we observed an association between good prognosis and HPV positivity, whereas adverse prognosis was associated with increasing both CRP levels and WBC counts. These are expected associations that have been described in previous studies [ 9 , 21 , 22 , 23 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 78 ] and therefore suggest that our patient cohort is representative. Furthermore, histopathological features like tumor lymphocyte density predict prognosis both in HPV-negative and HPV-positive oropharyngeal cancer patients [ 79 ].…”
Section: Discussionsupporting
confidence: 85%
“…Several previous studies have shown that both increased systemic CRP levels [ 8 , 47 , 48 , 49 , 50 , 51 , 52 ] and IL6 levels [ 9 , 21 , 22 , 23 , 53 , 54 , 55 , 56 , 57 ] are associated with an adverse prognosis in HNSCC. IL6 can function as a driver of the acute phase reaction, i.e., increased CRP levels can at least partly be due to an IL6 effect [ 1 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher sensitivity and specificity were obtained by measuring the levels of both IL-6 and IL-8. [ 83 ]. Similarly, Punyani and Sathawane analysed the salivary level of IL-8 in patients with premalignant oral lesions and OSCC and in a control group.…”
Section: Markers Of Inflammation In Osccmentioning
confidence: 99%
“…Other studies found that exogenous TNF-α induces the transition of inflammation in the tumor stroma [21]. On the other side, Schiegnitz et al [22] demonstrated that serum TNF-α level is not a useful associated or prognostic marker of oral squamous cell carcinoma patients as IL-6, IL-8, and soluble IL-2R. Conflicting results about the level of TNF-α relates to the methodology of each study.…”
Section: Discussionmentioning
confidence: 99%